THE UNIQUE CHARACTERISTICS OF THE AESTHETIC PHENOMENON OF HUMAN DIGNITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article on "The Unique Characteristics of the Aesthetic Phenomenon of Human Dignity" discusses the analysis of human dignity from an aesthetic perspective and its place in society. The aesthetic aspect of human dignity is presented, highlighting its connection not only to ethical and spiritual values but also to external appearance and aesthetic concepts. The article explores how the aesthetic approach to human dignity is expressed in art and culture, as well as how this concept aligns with personal and social characteristics. The aesthetic phenomenon plays an important role in creating a connection between a person’s inner world and the external environment, significantly influencing an individual’s self-awareness and their place in society. Additionally, the article delves into the aesthetic dimension of human dignity from both general and specific perspectives.